Crashworthiness analysis of octagonal multi-cell tube with functionally graded thickness under multiple loading angles. (January 2017) - Chen, Yafeng; Bai, Zhonghao; Zhang, Linwei; Wang, Yulong; Sun, Guangyong; Cao, Libo
Abstract: This paper provides a study on a novel octagonal multi-cell tube with functionally graded thickness (FGT) under multiple loading angles. First, comparative analysis on the FGT tube and the counterpart tube with uniform thickness(UT) under multiple loading angles reveal that the energy absorption is more superior for the FGT tube when the loading angle exceeds the lower bound of the transition range of the UT tube. Second, parametric study on the FGT tube indicates that thickness gradient exponent and thickness range have significant effect on its crashworthiness. Third, multiobjective optimizations of the FGT tube are conducted, aiming to maximize specific energy absorption(SEA) and minimize initial force(IPF) under multiple loading angles, based upon the Non-dominated sorting genetic algorithm(NAGA-Ⅱ) and RBF technique. The optimized FGT tube demonstrates better crashworthiness than the UT tube in all design cases. These findings can provide valuable guidelines for the design of multi-cell tube with functionally graded thickness under multiple loading angles. Highlights: A new octagonal multi-cell tube with functionally graded thickness is proposed. Comparative analysis on the new structure and the counterpart tube with uniform thickness under multiple loading angles. Design of multi-cell tube with functionally graded thickness under multiple loading angles.